PENINGKATAN KAPASITAS PELAYANAN AIR BERSIH DI BANJAR TANGKAS KECAMATAN SUSUT KABUPATEN BANGLI - Wirawan, I K. G.; Sucipta, M.; Suarda, M.; Muku, I.D.M.K. (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi)
“Udayana Mengabdi” a community service program that was initiated by the Udayana University, where the program is implemented at Banjar Tangkas with a population of 157 households or approximately 588 peoples. Almost all the people there can enjoy clean water. The distribution using the hydraulic ram to lift water from the source of a very steep topography, so the water distribution system constraints can be overcome. Based on the orientation and discussion in the field, obtained a description that people still have difficulty in obtaining information on the hydraulic ram, particularly in terms of maintenance and repair. To overcome this problem, was conducted the technical guidance regarding maintenance and repairs to community groups. Physically, the results of this activity can be seen in the form of making a safety lid springs are made of concrete slab, the objective is for durability and protect it from the leaves of trees. In addition, other results are in the form of a storage warehouse of spare parts pumps, in order to easily maintenance and repair.
Keywords: hydraulic ram, maintenance, repair, spare parts